(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research explores the role of professional development programs in shaping organizational culture and enhancing teaching effectiveness in higher education institutions. It aims to understand the mechanisms through which these programs contribute to a positive, growth-oriented culture among faculty members, using theoretical frameworks like Schein's model and adult learning theory. The study endeavors to examine the impact of organizational culture on teaching effectiveness, considering factors such as faculty engagement, collaboration, and innovation. By analyzing data collected from faculty members and administrators in higher education institutions in Bangalore, India, the research aims to provide insights into the design and implementation of effective professional development strategies tailored to the needs of diverse academic communities. The Study offering evidence-based recommendations for enhancing teaching quality through strategic investments in professional development programs. The findings are expected to inform institutional practices and policies aimed at fostering a culture of continuous learning and improvement within higher education contexts.